PERAN KOMUNITAS SOSIAL DALAM PRAKTIK FILANTROPI MELALUI KEWIRAUSAHAAN SOSIAL (Studi kasus terhadap Organisasi Greeneration Foundation) - Febri Saefulloh Saefulloh; Yoga Gandara Gandara (Pendidikan Sosiologi Universitas Sultan Ageng Tirtayasa, 2021)
Abstract This research has a background on social problems that occur in Indonesia. The problems that are often faced are not only in Indonesia but globally, starting from poverty, social inequality, unemployment, to individualistic behavior that does not care about the lives of fellow humans and the environment. This problem needs serious handling from all elements of society, including contributions from the social community. Greeneration Foundation is a social community formed from anxiety about human behavior that only cares about personal matters and does not pay attention to life in the future. Social entrepreneurship is a concrete philanthropic step carried out by this community. Through his programs and partnerships as the implementation of the vision of